Clarificação do suco de acerola por processo com membrana - Fernandes, Larissa Maria (1999)
In ultrafiltration the pressurized solution flows on a selective porous membrane, permeable to the solvent and to solutes of relatively low molecular weights, but impermeable to big molecules. It allows the simultaneous processing of division, concentration and purification of solutions with different components. The objective of the present work was the study of clarification of natural acerola juice by ultrafiltration process, using a 30K daltons regenerate cellulose spiral membrane, in the cross-flow module. To confirm that the pectine present in acerola juice causes the blockage of the membrane by forming a get at the surface, was carried out with the acerola enzyme-treated juice and the juice without treatment, observing the influence of the operation pressure on the filtrate flow rate. The results confirm that na increase in the pressure increases the filtrate flow rate and that the enzymatic treatment contributed to this increase, reducing the obstruction at he membrane surface.